SOURCES OF RADIOACTIVE WASTE IN LEACH PLANTS PROCESSING URANIUM ORES - R. E. Kuzin; S. N. Brykin; T. N. Tairov (Тонкие химические технологии, 2016)
A distinctive feature of enterprises for extracting and processing uranium ore is the inevitable pollution by solid, liquid and gaseous waste. The amount of radioactive waste (RW) is most significant in the nuclear fuel cycle. In spite of its relatively low activity it is the major contributor to the formation of radiation hazards to the people and environment. The radioactivity of uranium ores and of their processing waste is due to natural radionuclides of uranium (238U and 235U) and thorium (232Th) radioactive decay chains.